A view of global monsoons in observed and model climatology - SAHA, K.R.; DOOL , HUUG M. VAN DEN; SAHA, SURANJANA (MAUSAM, 1998)
A 17 - year (1979-95) January and July climatology obtained from a T 62/ 28 -level version of the National Centers for Environmental Prediction (NCEP) global spectral operational model is compared with a mean observed climatology for the same period obtained from its reanalysis project, with a view to finding out how well it captures some of the well-thrown characteristics of the global monsoon circulation generated seasonally by differential heating of the earth's surface by the sun in the course of its annual oscillation about the equator. Good correspondence between the two is found in the fields of mean monthly anomaly (deviation of monthly mean from the annual mean) of surface temperature, surface pressure, atmospheric circulation and total rainfall over most parts of the globe, barring a few exceptions mostly in circulation and rainfall. Large diversity in the distribution and intensity of monsoon found over different regions due to land-sea configurations, cold and warm ocean surfaces and high mountain ranges appears to be well reflected in model and observed climatology. However, the concept of a single equatorial trough moving from one hemisphere to the other to cause advance and onset of monsoon appears to fail especially over warm oceans, where there appears to be evidence in favour of two troughs, one in each hemisphere. It is the equatorial trough in the summer hemisphere that moves to bring up the monsoon in that hemisphere. There appears to be some evidence to suggest an east-west movement of monsoons between major continents and oceans.